Pilot study to evaluate the use of remote patient monitoring to guide the timing of valve intervention in patients with severe asymptomatic aortic stenosis (APRAISE-AS): study protocol for a randomised controlled trial delivered in two tertiary cardiac centres in the UK - James M Cotton; Derek Kyte; Nazish Khan; Winnie Chua; Larissa Fabritz; Richard P Steeds; Yongzhong Sun; Samir Mehta; Katie Kirkham; Philip Collis; Clive Stubbs; Mary Nulty (BMJ Open)
Introduction Aortic stenosis (AS) is common affecting >13% of adults over the age of 75 years. In people who develop symptoms, without valve replacement, prognosis is dismal with mortality as high as 50% at 1 year. In asymptomatic patients, the timing of valve intervention is less well defined and a strategy of watchful waiting is recommended. Many, however, may develop symptoms and attribute this to age related decline, rather than worsening AS. Timely intervention in asymptomatic severe AS is critical, since delayed intervention often results in poor outcomes. Proactive surveillance of symptoms, quality of life and functional capacity should enable timely identification of people who will benefit from aortic valve replacement. There are no data however, to support the clinical and cost effectiveness of such an approach in a healthcare setting in the UK. The aim of this pilot trial is to test the feasibility of a full-scale randomised controlled trial (RCT) to determine the utility of proactive surveillance in people with asymptomatic severe AS to guide the timing of intervention.Methods and analysis APRAISE-AS is a multi-centre, non-blinded, two-arm, parallel group randomised controlled trial of up to 66 participants aged >18 years with asymptomatic severe AS. Participants will be randomised to either standard care or standard care supplemented with the APRAISE-AS intervention. Primary outcomes will capture; adherence to and participant acceptability of the intervention, recruitment and retention rates, and completeness of data collection. The findings will be used to inform the sample size and most appropriate outcome measure(s) for a full-scale RCT and health economic evaluation.Ethics and dissemination Ethical approval was granted by the Black Country REC, reference: 22/WM/0214. Results will be submitted for publication in peer-reviewed journals and disseminated at local, regional and national meetings where appropriate.Trial registration number ISRCTN19413194 registered on 14.07.2023.